AB0368 Association of 25-Hydroxyvitamin D3 Serum Levels and Metabolic Parameters in Portuguese Patients with Established Rheumatoid Arthritis. (9th June 2015) - Bernardes, M.; Martins, M.J.; Rosa-Gonçalves, D.; Fonseca, R.; Madureira, P.; Vieira, R.; Aguiar, F.; Simões-Ventura, F.; Costa, L.
Abstract : Background: Patients with rheumatoid arthritis (RA) are at higher risk for adverse cardiovascular events, an increase which is not completely explained by the presence of traditional risk factors. Vitamin D is an essential steroid hormone with an important role on mineral metabolism, skeletal health and on the cardiovascular and immune systems. Vitamin D seems to play a protective role against cardiovascular diseases, insulin resistance and obesity. Objectives: To assess the relationship of 25(OH)vitamin D3 (25(OH)vit.D) serum levels with lipid and glucose metabolism parameters in a Portuguese population of patients with established RA. Methods: For this study, clinical features and peripheral blood samples were collected from a monitoring visit of consecutive RA patients. The exclusion criteria were the use of anti-diabetic and/or anti-dyslipidemic therapies. The Portuguese version of HAQ-DI and the disease activity score (DAS28 (4v;ESR)) were obtained. We measured the following laboratory parameters: ESR and CRP, serum levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), triglycerides, apolipoprotein A1 (Apo A1), apolipoprotein B (Apo B), lipoprotein a (lpa), insulin, fasting glucose and uric acid. TC/HDL cholesterol (atherogenic or Castelli index), LDL/HDL cholesterol and Apo B/Apo A1 ratios were calculated. Insulin resistance was also determined (HOMA-IR). Serum 25(OH)vit.D levels were measured and its status established (<30 ng/mL: deficiency; ≥30 ng/mL: normal levels). A multivariate analysis model was used for statistical analysis (IBM SPSS Statistics 21). Results: We evaluated 156 RA patients, 126 (81%) women, 27 (17%) obese, 66 (43%) with overweight, 85 (55%) under biologics, 71 (46%) under TNF-alpha blockers, 31 (20%) under vitamin D supplements, age 51±11 years, 13±10 years of disease duration, mean DAS28(4v) of 4.17±1.39 and a mean HAQ of 1.172±0.709. Rheumatoid factor was positive in 61% (95) of the patients and anti-cyclic citrullinated peptide (anti-CCP) antibodies were positive in 78% (122). Only 53 (34%) of the patients exhibited adequate 25(OH)vit.D levels and 102 (66%) were 25(OH)vit.D deficient. We verified that 25(OH)vit.D deficiency was associated with higher serum levels of insulin and lpa (p<0.05). Additionally, 25(OH)vit.D deficiency was also associated with higher values of Apo B/Apo A1 ratio (p<0.05). It was observed a tendency for the association of lower 25(OH)vit.D levels with lower ApoA1 levels (p=0.056) and higher insulin resistance (p=0.070) in the serum. All these associations were found after adjusting for age, body mass index, current HAQ and current DAS28(4V; ESR). Conclusions: Our analysis supports the hypothesis of an association between vitamin D and several disturbances in glucose metabolism and lipid profile in established RA patients. However, this cross-sectional study did not permit the establishment of a causal relationship. References: Joshua F. Baker, Nehal N. Mehta, Daniel G. Baker, et al. Vitamin D, metabolic dyslipidemia, and metabolic syndrome in rheumatoid arthritis. American J Med. 2012; 125: 1036.e9-1036.e15 Disclosure of Interest: None declared